Penggunaan Distribusi di Era Digital dalam Upaya Meningkatkan Volume Penjualan pada Toko Roti Sari Good Bakery Cimahi - Muhammad Januar Ramadhan; Tiris Sudrartono (IPM2KPE, 2023)
This research aims to analyze the use of distribution in the digital era in an effort to increase sales volume at the Sari Good Bakery Cimahi bakery. The method used in this research is descriptive qualitative. Qualitative research is generally used in social phenomenology. This research analyzes the relationship between the use of online distribution and sales volume. Observations were made to collect data using data collection techniques and interviews with research objects. The lowest sales were in July at 14,696 with a percentage of -33% and the highest sales were in March at 23,909 with a percentage of 20%. At the end of 2022, especially from August to December, sales at the Sari Good Bakery Bakery always experience a significant decline. Indirect distribution activities generally use intermediaries. With developments in the current digital era, the Sari Good Bakery shop is required to utilize digital technology. With the use of market places and digital media, distribution activities should become more efficient in the distribution process so that it will increase sales volume in Sari Good Bakery bakery. Keywords: Digital Distribution, Management, Marketing